SIKEPUL: Sistem Informasi Untuk Administrasi Transaksi Jual Beli Pengepul Rongsokan Menggunakan Metode Waterfall - Ika Dewi Rozaurrohmah; Lutfi Syafirullah; Oman Somantri (Journal of Innovation Information Technology and Application (JINITA), 2021)
Currently collector businessmen are experiencing problems, namely the absence of data collection for suppliers and collapsed transaction activities. In addition, the administrative data collection process is still carried out manually by the admin, , one of which is using notes when making junk transactions and when partners make payments to collectors, there are often communication errors in junk transactions between suppliers and partners often occur. In order to overcome the existing problems, this research proposes the development of a collector administration information system named SIKEPUL using the laravel framework. The method in developing the system used is the waterfall method. The results showed that the SIKEPUL information system could solve the problems faced. The overall results of the questionnaire for 30 respondents were that 20% said it was very good, 52% said it was good, and 28% said it was enough for this system.